Counselling and therapy techniques : theory and practice - Meier, Augustine , 1933-; Boivin, Michelin , 1950- (SAGE, 2011)
Counselling and Therapy Techniques covers all the major counselling approaches and provides all the tools required for developing a therapeutic relationship with clients